The Social Costs of Sounding Gay: Voice-Based Impressions of Adoption Applicants. (January 2020) - Fasoli, Fabio; Maass, Anne
In three studies (total N = 239) we examined the unexplored question of whether voice conveying sexual orientation elicits stigma and discrimination in the context of adoption. Studies 1 and 2 were conducted in Italy where same-sex adoption is illegal and controversial. Study 3 was conducted in the United Kingdom where same-sex adoption is legal and generally more accepted. The three studies show that listeners draw strong inferences from voice when judging hypothetical adoption seekers. Both Italian and British listeners judged gay-sounding speakers as warmer and as having better parenting skills, yet Italian participants consistently preferred straight over gay-sounding applicants, whereas British participants showed an opposite tendency, presumably reflecting the different normative context in the two countries. We conclude that vocal cues may have culturally distinct effects on judgment and decision making and that people with gay-sounding voices may face discrimination in adoption procedures in countries with antigay norms.